Core-scale geophysical and hydromechanical analysis of seabed sediments affected by CO2 venting. (June 2021) - Falcon-Suarez, Ismael Himar; Lichtschlag, Anna; Marin-Moreno, Hector; Papageorgiou, Giorgos; Sahoo, Sourav K.; Roche, Ben; Callow, Ben; Gehrmann, Romina A.S.; Chapman, Mark; North, Laurence
Highlights: Experimental assessment of CO2 venting through North Sea seafloor sediments. Joint geophysical-hydromechanical datasets to improve subseafloor CO2 monitoring. Enhanced porosity and saturation estimates from resistivity and composition. CO2 venting induces fracturing preferentially in fine-grained seafloor sediments. CO2 -induced fracturing reduces the retention capacity of sediments. Abstract: Safe offshore Carbon Capture Utilization and Storage (CCUS) includes monitoring of the subseafloor, to identify and assess potential CO2 leaks from the geological reservoir through seal bypass structures. We simulated CO2 -leaking through shallow marine sediments of the North Sea, using two gravity core samples from ∼1 and ∼2.1 m below seafloor. Both samples were subjected to brine−CO2 flow-through, with continuous monitoring of their transport, elastic and mechanical properties, using electrical resistivity, permeability, P-wave velocity and attenuation, and axial strains. We used the collected geophysical data to calibrate a resistivity-saturation model based on Archie's law extended for clay content, and a rock physics for the elastic properties. The P-wave attributes detected the presence of CO2 in the sediment, but failed in providing accurate estimates of the CO2 saturation. Our results estimate porosities of 0.44 and 0.54, a background permeability of ∼10 −15 and ∼10 -17  m 2, and maximum CO2 saturation of 18 % and 10 % (±5 %), for the sandier (shallower) and muddier (deeper) sample, respectively. The finer-grained sample likely suffered some degree of gas-induced fracturing, exhibiting an effective CO2 permeability increase sharper than the coarser-grained sample. Our core-scale multidisciplinary experiment contributes to improve the general interpretation of shallow sub-seafloor gas distribution and migration patterns.